Gene VIII-Based, Phage-Display Vectors for Selection Against Complex Mixtures of Ligands - Karin Jacobsson; Lars Frykberg (BioTechniques)
Selection of shotgun phage-display libraries against complex mixtures of components, such as cells or sera, may result in a high number of nonspecifically binding phage. Consequently, correct interactions may be difficult to identify. To enable discrimination between faithful and nonspecific interactions, a set of eight different gene VIII-based, phage-display vectors were constructed. All vectors contain a “universal” screening tag positioned in such a way that it is only expressed when the inserted DNA encodes an open reading frame, which corrects a shift of reading frames in the vector. A Staphylococcus aureus shotgun phagedisplay library was made in a stoichiometric mixture of all vectors. After affinity-selection against IgG, one vector completely outcompeted the others. This vector contains the promoter and signal sequence from the gene encoding staphylococcal protein A and one suppressible stop codon immediately upstream of gene VIII. An increase in the frequency of clones expressing the affinity tag in all pannings correlated with selection for ligand-binding clones. This enables detection of putatively correct clones after selection of a shotgun phagedisplay library both against purified ligands and more complex materials like calf serum.